Conservative Management of Congenital Muscular Torticollis: An Evidence-Based Algorithm and Preliminary Treatment Parameter Recommendations. - Christensen, Catie; Landsettle, Angela; Antoszewski, Sandra; Ballard, B. Blaire; Carey, Helen; Pax Lowes, Linda (Physical & Occupational Therapy in Pediatrics, 2013)
Purpose: To present an algorithm with accompanying treatment parameters for the management of congenital muscular torticollis (CMT) based on the best available literature. Methods: A systematic search of PubMed, MEDLINE, CINHAL, and Cochrane databases was conducted to identify evidence to guide the conservative management of CMT. Results: An evidence-based algorithm was created based on three prognostic factors that influence treatment duration and outcome, including a sternocleidomastoid fibrotic mass, passive range of motion rotation deficit, and age at initiation of treatment. Preliminary treatment parameter recommendations for clinic and home programming accompany the algorithm. Conclusion: Use of the proposed evidence-based algorithm with accompanying preliminary treatment parameter recommendations may improve consistency of care and outcomes for infants with CMT. While a higher level of evidence supports the three prognostic factors utilized in the algorithm, research gaps continue to exist with regards to treatment parameters.